Treatment of a penetrating inferior vena cava injury using doctor-helicopter emergency medical service and direct-to-operating room resuscitation in Korea: a case report - Dongmin Seo; Jieun Kim; Jiwon Kim; Inhae Heo; Jonghwan Moon; Kyoungwon Jung; Hohyung Jung (Journal of Trauma and Injury)
Inferior vena cava (IVC) injuries can have fatal outcomes and are associated with high mortality rates. Patients with IVC injuries require multiple procedures, including prehospital care, surgical techniques, and postoperative care. We present the case of a 67-year-old woman who stabbed herself in the abdomen with a knife, resulting in an infrarenal IVC injury. We shortened the transfer time by transporting the patient using a helicopter and decided to perform direct-to-operating room resuscitation by a trauma physician in the helicopter. The patient underwent laparotomy with IVC ligation for damage control during the first operation. The second- and third-look operations, including previous suture removal, IVC reconstruction, and IVC thrombectomy, were performed by a trauma surgeon specializing in cardiovascular diseases. The patient was discharged without major complications on the 19th postoperative day with rivaroxaban as an anticoagulant medication. Computed tomography angiography at the outpatient clinic showed that thrombi in the IVC and both iliac veins had been completely removed. Patients with IVC injuries can be effectively treated using a trauma system that includes fast transportation by helicopter, damage control for rapid hemostasis, and expert treatment of IVC injuries.